Fluorescence studies of benzothienoquinolines in lipid membranes - Oliveira, Andreia D. S. (2010)
This work was funded by FCT-Portugal through CFUM, CQ-UM, research project PTDC/QUI/81238/2006 (cofinanced by FEDER/COMPETE, FCOMP-01-0124-FEDER-007467) and National NMR Network (Bruker 400). FCT is also acknowledged for Ph.D. grant of R. C. Calhelha (SFRH/BD/29274/2006).